Pendekatan Joyful Learning Sebagai Metode Pembelajaran Pendidikan Kependudukan & Lingkungan Hidup (PKLH) di Madrasah Ibtidaiyah - Suriani Nur (Institut Agama Islam Negeri (IAIN) Bone, 2017)
Environmental damage is basically the state of the ecosystem is not in a normal state. Environmental problems arise due to human activities use the environment without regard to sustainability. If there is a disregard for the preservation of the environment, then people will feel the impact, both directly and indirectly. Madrasah as one of the first container and a major in the formation of man of faith and character, should support the Government in implementing education learning population and environment (PKLH). Therefore, in the learning environment needs to be designed such that students can learn the population and the environment in a relaxed, happy, and meaningful, so learning it is fun not a burden. PKLH correspond to the learning objectives, then the effective learning should use a variety of approaches that can be fun and attract the attention of students like Joyful Learning approach